PHONOLOGY AND WRITING: THE POSSIBLE THEORETICAL-METHODOLOGICAL RELATIONS AND CHALLENGES - Tenani, Luciani Ester [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2017)
This paper deals with studies about phonology and writing, aiming at two objectives. One objective is to draw a brief retrospective of pioneering studies in the 1980s which outlined possible paths of investigation, whereas the second objective, related to the first one, is to show developments achieved by subsequent research work done mainly in the first decades of the 2000s. We highlight studies which investigate the unconventional segmentation of words (such as de mais [too much], concerteza [certainly]) from a linguistic perspective conceiving them as students' hypotheses about word boundaries. These hypotheses are built from relations between speech and writing and reveal (possible) interactions between prosodic, morphosyntactic and semantic information about utterances. Our analysis comprises elementary school texts written by students in the process of acquisition and development of writing in a school environment. We argue in favour of an approach in which writing data provides the foundation for questioning assumptions which support phonological theories.
Keywords: phonology; prosody; writing